Korean Pop sebagai Identitas Subkultur iKONIC - Vania P Hanjani; Amirudin Amirudin; Mulyo Hadi Purnomo (Endogami: Jurnal Ilmiah Kajian Antropologi, 2019)
The popularity of Korean Pop culture can be used as a reference for adolescents to become a spear of maturity which ends in the formation of a subculture. We will discuss about how young people who gradually follow the development of iKON, a boygroup. They are willing to set aside most of the money they get, in order to fulfill their desire for satisfaction for iKON. iKON is a famous South Korean boy group that is currently very admired. This group has even won many awards and managed to become one of the closing guest stars of the well-known sports festival named ASIAN GAMES 2018 with their song Rhythm Ta and Love Scenario. With this phenomenon, more and more teenagers have decided to become iKONIC, an iKON fan community.This ethnographic and qualitative research will address the symbolic theory of interpretivism by Clifford Geertz which explains that culture is a system of regularity of meanings and symbols. With this meaning, each individual will communicate, establish, and develop knowledge about life as well as addressing life. Like teenagers who are members of the iKONIC community, they learn, receive and share the symbols from iKON. iKONIC will make iKON as a reference in doing everything in their lives. iKONIC is willing to buy many items related to iKON such as albums, merchandise, streaming passes, and even concert tickets that are very expensive. The more they are fond of the presence of iKON, the more they cling to the principles instilled by iKON. Their daily habits in imitating, accessing information continuously, result in their own dependence on them. The occurrence of many processes such as social contact, cultural understanding, the cognition system which became a symbol system, then shared, this is the reason existence of habits that continue to occur to become a culture for the iKONIC. So that a subculture is formed in the midst of a culture that has become widespread and entrenched.